Equilibrium Isotherm, Kinetic and Thermodynamic Studies of Cr (VI) onto Soil, Contaminated from Waste water of Textile Industry - Vijayvergiy Priya; Saxena Shweta (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The aim of this work was to study the adsorption of Chromium on dye contaminated soil and to give the best suited kinetic model, adsorption isotherm and to evaluate thermodynamic parameters, which are helpful to understand the interaction of chromium with soil. Adsorption studies have been done using a batch adsorption technique. The change in Cr (VI) concentration due to adsorption was determined by 1,5 Diphenylcarbazide spectrophotometric method. The measurements were made at the wavelength λ=540nm. The concentrations of chromium (VI) at different time adsorbed in soil solids were calculated. Soil before adsorption and after adsorption was characterized using SEM results revealed that adsorption rate increases in increasing initial chromium concentration and temperature of adsorption medium. The positive values of ∆G0 at all studied temperatures indicate that adsorption process is endergonic (non spontaneous). The values of ∆H0 and ∆S0 is found to be 14661.97 J/mol and 44.760 J/mol K respectively. The Langmuir and Freundlich isotherm were used to describe the adsorption equilibrium studies. The value of r2 for Langmuir and Freundlich is 0.517 and 0.985 respectively. From kinetic experiments, it was obtained that the sorption process followed the intraparticle diffusion model.